TINJAUAN ‘URF TERHADAP TRADISI NIKAH MALEM SONGO (Studi Kasus Di Desa Mergosari Kecamatan Singgahan Kabupaten Tuban) - Alvi Mafazatus Syauqiyah; Abdullah Afif (CV. KAMPUS AKADEMIK PUBLISING, 2025)
The month of Ramadan encourages Muslims to hasten in worship. In addition, the approach to Eid al-Fitr is often colored by many Islamic traditions, including Malam Songo. Malam Songo is a Javanese tradition on the 29th night of Ramadan which is believed to be a night that has many blessings. On Malam Songo in Mergosari Village, Singgahan, Tuban, there are many traditions such as breaking the fast and sending prayers together at the mosque and visiting the graves of parents and relatives. In general, this night is also considered as a good night for holding a wedding. This research is an empirical qualitative research, focuses on describing and understanding the practice and how the meaning of the Malam Songo through the ‘urf lens. In obtaining the data, the wroter used three data collections techniques which are namely interviews, observation, and documentation. Through the Sociology of Islamic Law approach in examining the study of legal understanding, it can be concluded that this tradition represents the peak of perfection. According to Islamic fiqh in practice, nikah malem songo has no different than marriage in general. Since the beginning, it is interpreted as a blessing that makes the household filled with grace, this tradition is accepted as a valid 'urf because the pillars and practices do not conflict with shari'a, more based on cultural efficiency such as ease of organizing events, strengthening friendship and not eliminating benefits or causing harm.